Resource conflict, collective action, and resilience: an analytical framework - Blake D. Ratner; Ruth Meinzen-Dick; Candace May; Eric Haglund (International Journal of the Commons, 2013)
Where access to renewable natural resources essential to rural livelihoods is highly contested, improving cooperation in resource management is an important element in strategies for peacebuilding and conflict prevention. While researchers have made advances in assessing the role of environmental resources as a causal factor in civil conflict, analysis of the positive potential of collective natural resource management efforts to reduce broader conflict is less developed. Addressing this need, we present a framework on collective action, conflict prevention, and social-ecological resilience, linking local stakeholder dynamics to the broader institutional and governance context. Accounting for both formal and informal relationships of power and influence, as well as values and stakeholder perceptions alongside material interests, the framework aims to provide insight into the problem of (re)building legitimacy of common-pool resource management institutions in conflict-sensitive environments. We outline its application in stakeholder-based problem assessment and planning, participatory monitoring and evaluation, and multi-case comparative analysis.